2018
DOI: 10.1186/s12889-018-5911-x
|View full text |Cite
|
Sign up to set email alerts
|

Low potassium and high sodium intakes: a double health threat to Cape Verdeans

Abstract: BackgroundCape Verde presents a high rate of cardiovascular diseases. Low potassium and high sodium intakes are related to cardiovascular diseases. However, studies regarding these two micronutrients continue to be rare in African urban settings. This work aims to estimate potassium and sodium intakes and to analyse the self-reported salt intake by gender and by type of urban area in the city of Praia – the capital of Cape Verde.MethodsIn the first stage (n = 1912), an intra-urban study was designed in two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…This review showed that sodium intake and excretion were generally higher in men than in women 29,31,34,35,59 . This difference may be due, at least in part, to sex differences in energy intake 63 .…”
Section: Discussionmentioning
confidence: 95%
“…This review showed that sodium intake and excretion were generally higher in men than in women 29,31,34,35,59 . This difference may be due, at least in part, to sex differences in energy intake 63 .…”
Section: Discussionmentioning
confidence: 95%
“…While African regions in general are reported to have lower sodium intake compared to other world regions, the average amount consumed across all African regions is above the WHO recommended intake guidelines (1,3). Where studies have assessed intake in specific African countries, the reported salt intake is more comparable or above to the mean global intake level of 9-10 g/day (4)(5)(6)(7)(8)(9). Furthermore, sodium intake is likely to rise in African populations in the future (similar to other developing countries) as dietary patterns transition to a higher proportion of processed and convenience foods (10,11).…”
Section: Dietary Sodium Intake and Bouillon In Sub-saharan Africa Afr...mentioning
confidence: 92%
“…Ingestion of a certain amount of dietary fiber apart from alleviating constipation also reduces hunger, thereby reducing total energy intake and preventing weight gain [40]. Additionally, prior research stated that low vitamin C intakes may put people at risk of developing clinical scurvy, which is fatal if left untreated [41] and low potassium intakes increase the risk of people for hypertension and other cardiovascular diseases [42]. Lower sodium and sugar intakes were also observed among Filipinos with the healthiest diet quality (tertile 3).…”
Section: Commonly Consumed Food and Nutrient Intakes At Breakfast In ...mentioning
confidence: 99%